Accounting and financial management in foodservice operations - Hayes, David K.; Ninemeier, Jack D. (Hoboken, New Jersey John Wiley & Sons, Inc., 2024)
"The purpose of this book is to teach foodservice operators how they can use accounting and financial management techniques, as well as their own education, experience, values, and goals to make the very best management decisions possible for the businesses they manage. Every foodservice operation must offer high quality menu items and provide excellent service to its guests, but these factors are still not enough to ensure an operation's long-term financial success. How foodservice operators account for their revenue and expenses and manage their money are critical factors to reaching their financial objectives. It is important to understand that proper accounting alone cannot "make" the managerial decisions required of foodservice operators. It can, however, help operators make better decisions than those made by operators who do not understand how proper accounting procedures could help them"--
Includes index.
Keywords: Food service -- Accounting; Food service -- Cost control; Food service -- Finance